Pincer nail deformity in a patient with amyotrophic lateral sclerosis - Youshi Fujita; Takehisa Fujita (MDPI AG, 2014)
Although several manifestations of skin involvement in cases of amyotrophic lateral sclerosis (ALS) have been reported, the pincer nail deformity has not been previously reported in a patient with ALS. The pincer nail deformity is characterized by distortion of the shape of the nail with transverse over curvature and may be associated with systemic diseases and certain medications. We herein describe the case of a patient presenting with a pincer nail deformity associated with rapidly advancing ALS. This case suggests a potential link between quickly advancing disease and the pincer nail deformity.